2011
DOI: 10.1128/jb.00015-11
|View full text |Cite
|
Sign up to set email alerts
|

Surface Localization Determinants of Borrelia OspC/Vsp Family Lipoproteins

Abstract: The dimeric OspC/Vsp family surface lipoproteins of Borrelia spirochetes are crucial to the transmission and persistence of Lyme borreliosis and tick-borne relapsing fever. However, the requirements for their proper surface display remained undefined. In previous studies, we showed that localization of Borrelia burgdorferi monomeric surface lipoprotein OspA was dependent on residues in the N-terminal "tether" peptide. Here, site-directed mutagenesis of the B. burgdorferi OspC tether revealed two distinct regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 72 publications
4
46
0
Order By: Relevance
“…In a related set of experiments, we identified the molecular basis of a recent observation regarding B. burgdorferi OspC secretion, where periplasmic or C-terminally tagged mutants of OspC produced a lower-molecular-mass variant that apparently resulted from C-terminal cleavage (28). Our results indicate the following.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…In a related set of experiments, we identified the molecular basis of a recent observation regarding B. burgdorferi OspC secretion, where periplasmic or C-terminally tagged mutants of OspC produced a lower-molecular-mass variant that apparently resulted from C-terminal cleavage (28). Our results indicate the following.…”
supporting
confidence: 59%
“…Expression of a C-terminally hexahistidine-tagged OspC (OspC-His) also yielded an OspC* band that did not react with a His epitope-specific antibody or Ni 2ϩ conjugate. We therefore concluded that OspC* resulted from C-terminal cleavage (28). This evoked the C-terminal processing of P13 and hinted at the involvement of a similar, if not identical, processing pathway.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, we were able to demonstrate that the same OspA-CaM fusion proteins that were restricted to the periplasmic leaflet of the OM under experimental conditions that favored folding regained their capacity to be translocated through the OM under experimental conditions that induced unfolding. These findings are in accordance with our earlier interpretations of individual sets of OspA and OspC lipoprotein mutant phenotypes, where periplasmic OspA and OspC tether mutants could be redirected to the bacterial surface by mutational destabilization of a C-terminal ␣-helix or by the addition of short disordered C-terminal epitope/affinity tags, respectively (32,50). Interestingly, the present study reiterates that C-terminal structural destabilization, achieved this time by chelating Ca 2ϩ from an admittedly larger calmodulin "tag," is sufficient to promote secretion through the OM.…”
Section: Discussionsupporting
confidence: 81%
“…We found that established eubacterial lipoprotein-sorting rules governed by N-terminal residues proximal to the triacyl-modified cysteine did not apply (22,37,40,52,53,58). Yet lipoprotein-targeting instructions remained restricted to disordered N-terminal peptides that function as "tethers," i.e., that link the folded domains of the protein to the triacyl membrane anchor (32,33,50,51) (Fig. 1).…”
mentioning
confidence: 99%